2014
DOI: 10.1001/jamapediatrics.2014.895
|View full text |Cite
|
Sign up to set email alerts
|

Blood Culture Time to Positivity in Febrile Infants With Bacteremia

Abstract: IMPORTANCE Blood cultures are often obtained as part of the evaluation of infants with fever and these infants are typically observed until their cultures are determined to have no growth. However, the time to positivity of blood culture results in this population is not known.OBJECTIVE To determine the time to positivity of blood culture results in febrile infants admitted to a general inpatient unit. DESIGN, SETTING, AND PARTICIPANTS Multicenter, retrospective, cross-sectional evaluation of blood culture tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 31 publications
(37 reference statements)
4
75
0
1
Order By: Relevance
“…Sixtyfive percent of positive blood cultures deemed to be contaminants had inadequate blood volume (13), and recovery of contaminant was twice as likely when inadequate blood volume was obtained (5.1% versus 2.8%) (12). These findings further support the necessity of obtaining sufficient blood culture volume, as the recovery of contaminants has been reported in 25% to 69% of all positive blood cultures in pediatric patients (12)(13)(14) and is associated with unnecessary antimicrobial therapy, prolonged hospitalization, and incurred cost. It is not particularly clear why low volume blood cultures are more prone to yield contaminants; one theory is that the acquisition of contaminants is independent of blood volume, and rather the collection of larger blood volume dilutes the concentration of the contaminant present in the blood culture bottle, reducing the chance of detection during the incubation period (13,15).…”
Section: Blood Culture Collectionmentioning
confidence: 57%
“…Sixtyfive percent of positive blood cultures deemed to be contaminants had inadequate blood volume (13), and recovery of contaminant was twice as likely when inadequate blood volume was obtained (5.1% versus 2.8%) (12). These findings further support the necessity of obtaining sufficient blood culture volume, as the recovery of contaminants has been reported in 25% to 69% of all positive blood cultures in pediatric patients (12)(13)(14) and is associated with unnecessary antimicrobial therapy, prolonged hospitalization, and incurred cost. It is not particularly clear why low volume blood cultures are more prone to yield contaminants; one theory is that the acquisition of contaminants is independent of blood volume, and rather the collection of larger blood volume dilutes the concentration of the contaminant present in the blood culture bottle, reducing the chance of detection during the incubation period (13,15).…”
Section: Blood Culture Collectionmentioning
confidence: 57%
“…23 In total, 392 cultures were identifi ed from 17 sites for analysis. Figure 1 displays the geographic distribution of culture collection from our sample, with the largest number of cultures collected in Minnesota, Texas, Ohio, and Colorado, representing a fairly diverse geographic sample.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of culture inclusion and exclusion criteria, including full methodology of the epidemiology aspect of the cultures, has been previously published. 23 Cultures were included for analysis if they were positive for bacteria, obtained from an infant 90 days of age or younger with a temperature ≥38°C recorded on presentation or reported by a caregiver, analyzed using an automated bacterial detection system, and treated as a pathogen by the medical team (defi ned as a full course of antibiotics intended to treat the bacteria identifi ed in culture). Cultures were excluded if they were drawn in any method other than peripheral venipuncture, obtained from a patient in the ICU or admitted to the ICU within 5 hours after the culture, from patients with central indwelling catheters or hardware, or with a history of intraabdominal, intracranial, or intrathoracic comorbidities or surgical procedures, or drawn from a hospital or clinic outside the system of any participating site.…”
Section: Methodsmentioning
confidence: 99%
“…7,[33][34][35][36][37][38] The extreme rarity of listeriosis without meningitis after the first week of life in our study is consistent with and supported by previous studies that analyzed fever evaluations in neonates and young infants. 9,13, 16,17,39 Previous studies showed that listeriosis disproportionately affects the poor, but these did not specifically look at this phenomenon in young infants. 40,41 We found that infants with Medicaid (versus private) insurance 42 and infants living in a lower-income household were overrepresented among those discharged for listeriosis (see Table 1).…”
Section: Discussionmentioning
confidence: 99%